Pengaruh Pelatihan, Pengalaman Kerja, Lingkungan Kerja, dan Kompetensi Terhadap Kinerja Pegawai Badan Penanggulangan Bencana Daerah Kabupaten Labuhanbatu - Nela Rosa; Yuniman Zebua; Muhammad Raja Siregar (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This research aims to determine the influence of training, work experience, work environment and competency on the performance of employees of the Labuhanbatu Regency Regional Disaster Management Agency. This type of research is associative research. Data collection in this research was carried out using a survey approach with a quantitative descriptive research type by distributing questionnaires to 30 respondents. The data analysis tool used in this research uses SPSS (Statistical Product Software Solution). The data analysis techniques in this research are descriptive analysis, multiple linear regression analysis, hypothesis testing using a partial significant test (t test), simultaneous significant test (F test), and testing the coefficient of determination (R2). The results of this research show that training, work experience, work environment and competence influence the performance of employees of the Labuhanbatu Regency Regional Disaster Management Agency both partially and simultaneously.